Réponses

2013-04-01T14:16:39+02:00

 

1. M = (2x+3)² + (2x+3)(7x-2)

M =  (2x+3)(2x+3) + (2x+3)(7x-2)

M = 4x² + 6x + 6x + 9 + 14x² - 4x + 21x - 6

M = 18x² + 29x + 3

 

2. M = (2x+3)² + (2x+3)(7x-2)

M =  (2x+3)(2x+3) + (2x+3)(7x-2)

M = (2x+3) (2x + 3 + 7x -2)

M = (2x+3) (9x+1)

 

3. M = (2x+3) (9x+1)

M = (2*(-4)+3) (9*(-4)+1)

M = (-8+3) (-36+1)

M = 288-8-108+3

M=175

 

Exercice 4 :

1. N = (x+5)² - (x-5)²

N = x²+2*x*5+5² - (x²-2*x*5+5²)

N= x² + 10x+25 - (x²-10x+25)

N= x² + 10x+25-x²+10x-25

N = 20x

 

2.a. N = 20*x

N = 20*0

N=0

 

b. N = 20*x

N=20*1

N=20

 

c. N=20*x

N= 20 * (-2)

N = -40